Factors influencing seizure control of patients with convulsive epilepsy in rural areas of northwest China - Xiao Guan; Yuanyuan Wang; Xuan Wang; Dianwei Wu; Xiaojing Shi; Changgeng Song; Zhongqing Sun; Lei Ma; Wen Jiang (Epilepsia Open)
Abstract Objective The efficacy of the community‐based epilepsy management program has been validated in rural regions of China. However, a considerable proportion of patients with epilepsy in these areas continue to experience adverse outcomes. This study aims to investigate the factors influencing seizure control among patients with convulsive epilepsy in rural areas of Shaanxi Province, Northwest China. Methods Participants enrolled in the Rural Epilepsy Prevention and Management Project in Shaanxi Province between January 2012 and September 2020 were included in this cross‐sectional study. Baseline sociodemographic, clinical characteristics, and epilepsy‐related psychological concerns were collected. Patients were categorized based on seizure reduction compared to the baseline over the past year: Group with controlled seizures and group with uncontrolled seizures. Multivariate logistic regression was used to identify factors associated with seizure control. Results The study included 1242 patients (714 males, 57.5%), with a median age of 48.0 (36.0, 58.0) years. Compared to the baseline seizure frequency, 462 (37.2%) were seizure‐free. Our analysis revealed that patients with higher annual income (≥24 000 RMB, OR, 0.58, 95% CI 0.40–0.84, p < 0.001), and those receiving phenobarbital monotherapy (OR, 0.66, 95% CI 0.49–0.90, p < 0.05) were more likely to achieve seizure control. In contrast, higher baseline seizure frequency (≥24 per year, OR, 2.06, 95% CI 1.59–2.66, p < 0.001), more adverse drug reactions (OR, 2.07, 95% CI 1.61–2.66, p < 0.001) and higher psychological concerns (OR, 1.89, 95% CI 1.44–2.48; p < 0.001) negatively impacted seizure control. Significance Low annual income, high baseline seizure frequency, multiple adverse drug reactions, and high psychological burden may negatively affect seizure control in epilepsy patients in rural areas. Strengthening socioeconomic support, improving access to medications, and incorporating psychological interventions may be crucial to enhancing seizure control and overall outcomes for patients in these regions. Plain Language Summary The epilepsy management program in the rural areas of Northwest China has achieved some success, with about 37% of patients achieving one year of seizure freedom. However, some patients still struggle to effectively control their seizures. Nearly 90% of patients experience psychological concerns related to epilepsy, with the greatest concern being epilepsy recurrence. The heavier the psychological concern, the more difficult it is to control seizures.